PERLINDUNGAN HUKUM TERHADAP PENGGUNA KARTU XL ATAS PRODUK YANG TIDAK SESUAIDENGAN YANG DIIKLANKAN - Sri Divia Bella; Zulfikar Jayakusuma; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Consumer products (consumer goods / services that are generally used to meet the needs of consumers) have become increasingly sophisticated both in technology and in appearance. On the other hand, people understand a consumer product as far as what the sellers / or business actors convey. High and low regarding the understanding of the quality of the product depends on the level of truth of the information conveyed by the seller / entrepreneur and the level of the consumer's ability to capture. This information can be in the form of oral or written information contained in brochures and pamphlets, labels, advertisements and so on. The materials can be so detailed that they are often